Physiotherapy techniques used in injury treatment: A systematic review of tennis elbow - Simplicio, Claudio Lopes; Purita, Joseph; Murrell, William; Santos, Gabriel Silva; dos Santos, Rafael Gonzales; Lana, JosÃ© FÃ¡bio Santos Duarte (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. This review provides a comprehensive analysis of the physiotherapy methods used to treat tennis elbow, emphasizing the importance of understanding its pathophysiology and etiology to inform effective treatment strategies.Material and Methods. This review explores a range of physiotherapy interventions, including manual therapies that alleviate pain and improve joint function. Techniques such as joint mobilization, soft tissue massage, and myofascial release are highlighted. Additionally, exercise rehabilitation plays a key role, with individualized exercise programs designed to strengthen weakened muscles and improve elbow biomechanics. The study utilized the Harzing Publish or Perish application for its literature search, sourcing relevant studies from Google Scholar and PubMed using keywords like "Cyriax," "myofascial release," "tendinitis," "trigger points," "tennis elbow," and "degeneration." Boolean operators "WITH," "AND," and "OR" were employed to refine the search results.Results. Various physiotherapy approaches, including manual therapy, the Cyriax method, deep friction massage (DFM), Mill manipulation, myofascial release techniques, laser therapy, pulse shortwave diathermy, and ultrasound, have demonstrated positive outcomes in reducing pain, enhancing function, and promoting tissue repair.Conclusion. In conclusion, this review emphasizes the critical role physiotherapy plays in the effective management of tennis elbow. By compiling the latest research and best practices, it offers valuable insights for practitioners seeking to improve patient outcomes for this prevalent and disabling condition.